1651 Va. Acts 365, Articles At The Surrender Of The Country, art. 13 - (:unkn) unknown (My University, 1651)
That all ammunition, powder and arms, other than for private use shall be delivered up, security being given to make satisfaction for it.
Keywords: GUNPOWDER - STORAGE